Pathomorphology Associated with Verminous Pneumonia and Hydatidosis in Goats - Singh Bhullar, Gurjit; Dev Singh, Nittin (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Pneumonia is a significant cause of mortality in goats. This study reports pulmonary parasitic infections with lung worm and hydatidosis  as the underlying cause of pneumonia in goats. A total of 11 carcasses with a history of pneumonia were necropsied at Ludhiana,  during January 2024 to March 2025. The etiological diagnosis was made using pathomorphological techniques. Out of 11 goats, 7 were  found to be positive for parasitic pneumonia, out of which 4 cases were found to be positive for verminous pneumonia and 3 cases for  hydatidosis. On post-mortem examination, verminous pneumonia revealed white spots of emphysema that were raised, well-defined,  and irregularly bordered and the caudal lobes of the lungs had subpleural, multifocal nodules (2-5 mm) which were clearly visible.  Hydatidosis revealed the presence of single to multiple cysts, sometimes covering the whole of the lung. The cysts were irregular  or oval in shape, varied in number, and ranged in dimension from 2 to 10 cm. They were often surrounded by a fibrous capsule. On  histopathological examination, verminous pneumonia revealed that in the bronchi lumen, a parasite cross-section was surrounded by  a thin exoskeleton made of chitin, a considerable number of parasitic eggs, inflammatory cells mostly eosinophils, foreign body giant  cells and neutrophils. In case of hydatidosis, the inner cyst wall consisted of a striated, hyalinized, eosinophilic layer (laminated layer)  free of epithelial cells. The lung parenchyma around the cyst was distorted and collapsed, the pulmonary epithelium was atrophied,  and mononuclear cells infiltrated the lung parenchyma. These findings signify the importance of parasitic control and routine health  monitoring to prevent the impact of parasitic pneumonia.
Keywords: Goat; Hydatidosis; Parasitic; Verminous